Advanced methodologies and technologies in media and communications - Khosrow-Pour, Mehdi, 1951- (Advances in multimedia and interactive technologies (AMIT) book series., 2019)
"This book provides emerging research on the modern effects of media on cultures, individuals, and groups. While highlighting a range of topics such as social media use and marketing, media influence, and communication technology, this book explores how these advancements shape and further the global society"--